Предмет: Математика,
автор: умен1
ctg(3arccos(-1)-arcsin(-1/2))
Ответы
Автор ответа:
0
Решение
Ctg(3arccos(-1)-arcsin(-1/2)) = ctg[(3*π) - (- π/6)] = ctg(19π/6) = ctg(2π + π/6) =
= ctg(π/6) = √3
Ctg(3arccos(-1)-arcsin(-1/2)) = ctg[(3*π) - (- π/6)] = ctg(19π/6) = ctg(2π + π/6) =
= ctg(π/6) = √3
Похожие вопросы
Предмет: Алгебра,
автор: liza29939393330
Предмет: Химия,
автор: kurmanbekovadina2006
Предмет: Информатика,
автор: glebkabest113243
Предмет: Литература,
автор: kolkatya
Предмет: Алгебра,
автор: WKOJlHIK